2004
DOI: 10.1093/humrep/deh082
|View full text |Cite
|
Sign up to set email alerts
|

Menses, fertility and pregnancy after arterial embolization for the control of postpartum haemorrhage

Abstract: Our results suggest that women who undergo arterial embolization for obstetric haemorrhage should expect to have a return of normal menses with preservation of future fertility and successful uneventful pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
1
10

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(60 citation statements)
references
References 20 publications
4
45
1
10
Order By: Relevance
“…Several studies demonstrated normal menses and pregnancies in women after arterial embolization. 16,[36][37][38] The fi ndings of the present study, though limited to a small number of subjects, support the benefi cial effects of arterial embolization with an adequately sized gelatin sponge for preserving reproductive function.…”
Section: Group 2: Prophylactic Catheterization For Anticipated Postpasupporting
confidence: 73%
“…Several studies demonstrated normal menses and pregnancies in women after arterial embolization. 16,[36][37][38] The fi ndings of the present study, though limited to a small number of subjects, support the benefi cial effects of arterial embolization with an adequately sized gelatin sponge for preserving reproductive function.…”
Section: Group 2: Prophylactic Catheterization For Anticipated Postpasupporting
confidence: 73%
“…Nonetheless, the radiation exposure appears to be comparable with that of routine diagnostic imaging procedures [32]. In one study [33], 10 pregnancies occurred in 25 patients after embolization therapy for postpartum hemorrhage. Those authors concluded that women who undergo arterial embolization for obstetric hemorrhage can preserve their fertility and have successful uneventful pregnancies.…”
Section: Discussionmentioning
confidence: 96%
“…All consecutive women with PPH who underwent embolisation as either the sole procedure (Group A) or in combination with uterine-sparing surgery (Group B) at our tertiary obstetric centre (Rouen University Hospital) between May 1994 and July 2007 were included in the study. The long-term maternal outcomes of the initial 28 participants treated between 1994 and July 1999 have been reported previously, 26 and the other women included up to July 2007 were added to the present study. The short-term maternal outcomes of these consecutive women have been reported previously in an earlier article.…”
Section: Methodsmentioning
confidence: 97%